Effect of Biopipe Total Flowrate on Venturi Aerator Performance - Jasem, Hayder M.; Khudair, Kifah M. (Basrah Journal for Engineering Sciences, 2023)
There is a vacuum created when water goes past a pipe constriction. Air may be pulled into the main flow by drilling a hole in the pipe near where the vacuum happens. Venturi aerator is an example of the application in action. A vacuum is formed at the suction holes of the Venturi tube when there is a small difference in pressure between the input and output sides. To demonstrate the link between total flow rate and Venturi aerator performance, a Venturi aerator (model 1584) was introduced at a specific point in a Biopipe system. For this purpose, a physical model on a pilot scale was constructed and installed in an existing sewage treatment plant. Dissolved oxygen concentrations were measured at four locations along the Biopipe at different values of wastewater flowrates. The study results showed that raising the total flow rate increased the amount of air injected by the Venturi aerator. When the total flow rate was less than 4 m 3 /hour, the Venturi aerator stops sucking air and produces negative consequences.